Linking knowledge, attitudes, and practices to disease dynamics in tilapia (Oreochromis niloticus) aquaculture on Volta Lake - Baah, Doris Y.; Edziyie, Regina; Gamil, Amr A.A.; Obirikorang, Kwasi Adu; Evensen, Øystein (Frontiers in Aquaculture, 2026)
IntroductionTilapia (Oreochromis niloticus) aquaculture accounts for nearly 80% of Ghana’s farmed fish production, with cage culture on Volta Lake as the dominant system. In recent years, production has been severely constrained by high disease-related mortalities, notably due to Streptococcus agalactiae and Infectious Spleen and Kidney Necrosis Virus (ISKNV). This study investigated how farm management practices and farmers’ knowledge, attitudes, and perceptions influence disease dynamics on Volta Lake.MethodsA cross-sectional survey of 56 farms across five districts was conducted using semi-structured questionnaires and interviews with farmers and the local fish health officer. Results showed that disease outbreaks were reported in all farms, with mortalities ranging from 10-80%.ResultsFarmers attributed outbreaks primarily to pathogens, but also to poor water quality, high stocking densities, and inadequate biosecurity. Diagnostic practices varied, with most farmers relying on clinical signs or peer consultation rather than laboratory testing. Clinical signs commonly reported included exophthalmia, swollen abdomens, and skin lesions. Farm management practices such as grading, sourcing of fingerlings, water quality monitoring, and biosecurity were inconsistent and largely unstandardized. Regression analysis indicated that stocking density, biosecurity, and water quality monitoring did not significantly predict disease-related mortality, underscoring the multifactorial nature of outbreaks in this open water system.DiscussionThe findings highlight the need for coordinated extension services, accessible diagnostic facilities, and standardized farm management protocols to strengthen disease prevention and control in Ghana’s cage aquaculture sector.